Federalism on trial : state attorneys general and national policymaking in contemporary America - Nolette, Paul (University Press of Kansas, 2015)
""It is one of the happy incidents of the federal system, "" Justice Louis Brandeis wrote in 1932, ""that a single courageous state may, if its citizens choose, serve as a laboratory, and try novel social and economic experiments without risk to the rest of the country."" It is one of the features of federalism in our day, Paul Nolette counters, that these ""laboratories of democracy, "" under the guidance of state attorneys general, are more apt to be dictating national policy than conducting contained experiments. In Federalism on Trial, Nolette presents the first broadscale examination of the.